2020
DOI: 10.1111/bjd.18879
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of paediatric localized scleroderma on health‐related quality of life: focus groups with youth and caregivers

Abstract: Background Paediatric localized scleroderma (LS) can negatively impact healthrelated quality of life (HRQoL) by causing skin fibrosis, abnormal limb development, disfigurement, and side-effects from immunosuppressive treatment. Studies to date have rarely included qualitative data gathered directly from paediatric patients with LS. Objectives To assess the impact of LS on HRQoL among affected youth and their caregivers using qualitative description. Methods Youth with all subtypes of LS and their caregivers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Interestingly, this finding was common across age groups of school-age and teenage children, as well as young adults. Anxiety and uncertainty linger even in remission, highlighting the need for longterm psychosocial support and confirming prior studies in JM regarding the rollercoaster of emotional distress (5,15,22). Our findings also replicate those of prior studies demonstrating high emotional distress in parents caring for children with JM, juvenile-onset SLE, and JIA, as well as negative impacts on siblings and family relations (7,22,24).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, this finding was common across age groups of school-age and teenage children, as well as young adults. Anxiety and uncertainty linger even in remission, highlighting the need for longterm psychosocial support and confirming prior studies in JM regarding the rollercoaster of emotional distress (5,15,22). Our findings also replicate those of prior studies demonstrating high emotional distress in parents caring for children with JM, juvenile-onset SLE, and JIA, as well as negative impacts on siblings and family relations (7,22,24).…”
Section: Discussionsupporting
confidence: 87%
“…Children with other chronic illnesses experience similar levels of life satisfaction as healthy children, although psychological stress is a negative predictor of such life satisfaction (28). Prior studies of patients with JM, their parents, and other pediatric rheumatic disease populations have also documented such post traumatic growth, although resiliency may wane with disease flares (5,7,15,22). While our findings add to emerging literature identifying resiliency in patients with JM, our study was not designed to identify specific family, parent, and child-level mechanisms contributing to resilient emotional health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoid medications offer potential for rapid clinical improvement, but frequently lead to side effects that adversely impact HRQOL. Many studies looking at the patient experience within paediatric rheumatic diseases, have found the burden of glucocorticoid treatment to be a recurring theme [ 14 17 ]. These range from short-term effects that may go unrecognised by clinicians (e.g., weight gain, anxiety, skin changes and poor sleep) to long-lasting adverse events (e.g., delayed growth and puberty, diabetes, loss of bone mass and fractures) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%